A comparison of diversity and species composition of ground beetles (Coleoptera: Carabidae) between conifer plantations and regenerating forests in Korea. Issue 5 (8th July 2014) - Jung, Jong‐Kook; Kim, Seung‐Tae; Lee, Sue Yeon; Park, Chang‐Gyu; Park, Jong‐Kyun; Lee, Joon‐Ho
Abstract: Ground beetles were collected by pitfall trapping to compare their species richness between conifer plantations (14 sites) and regenerating forests (14 sites) and among forest ages and to examine how different functional groups responded to forest type, forest age, patch size, elevation, and geographic location in terms of abundance and richness. Ground beetles were collected from middle August to late October, 2008. A total of 34 species were identified from 3, 156 collected ground beetles. Individual‐based rarefaction curves showed greater species richness in regenerating forests, especially in 40–50‐year‐old forests, than in conifer plantations. Stepwise multiple regression analysis showed that patch size and elevation were major predictors of species richness and/or abundance of forest specialists, brachypterous species, and large‐ and medium‐bodied species. A multivariate regression tree indicated that patch size and elevation were major predictors of assemblage structure. Although our results suggest that maintaining forest areas adjacent to agricultural landscapes may be essential to preserve ground beetle assemblages irrespective of forest types, further study is necessary to clarify the effects of habitat quality and amount on ground beetles in forests.